2021
DOI: 10.3390/life11111216
|View full text |Cite
|
Sign up to set email alerts
|

Protective or Risk Factors for Postoperative Pancreatic Fistulas in Malignant Pathology

Abstract: Introduction: Malignant tumors are associated with a low incidence of postoperative pancreatic fistulas. The presence of peritumoral fibrosis is considered the protective factor for the development of postoperative pancreatic fistulas after pancreatic resections for pancreatic ductal adenocarcinomas. Methods: We analyzed a series of 109 consecutive patients with pancreatic resections for malignant pathology: pancreatic ductal adenocarcinomas and periampullary adenocarcinomas. The incidence of postoperative pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
1
0
4
Order By: Relevance
“…Однак, незважаючи на важливість цих ускладнень, тільки в 2005 році було розроблено загальноприйняте визначення ППФ та їх стадіювання [2,4]. Щодо факторів ризику розвитку цих ускладнень, то вони все ще відрізняються у різних авторів [1,3,8,9,10,16,18]. Більшість з них як основні фактори ризику виділяють: вік, стать, індекс маси тіла (ІМТ), тип панкреатодигестивного анастомозу, щільність підшлункової залози, крововтрату під час операції, наявність механічної жовтяниці перед операцією та ін.…”
Section: вступunclassified
See 3 more Smart Citations
“…Однак, незважаючи на важливість цих ускладнень, тільки в 2005 році було розроблено загальноприйняте визначення ППФ та їх стадіювання [2,4]. Щодо факторів ризику розвитку цих ускладнень, то вони все ще відрізняються у різних авторів [1,3,8,9,10,16,18]. Більшість з них як основні фактори ризику виділяють: вік, стать, індекс маси тіла (ІМТ), тип панкреатодигестивного анастомозу, щільність підшлункової залози, крововтрату під час операції, наявність механічної жовтяниці перед операцією та ін.…”
Section: вступunclassified
“…Більшість з них як основні фактори ризику виділяють: вік, стать, індекс маси тіла (ІМТ), тип панкреатодигестивного анастомозу, щільність підшлункової залози, крововтрату під час операції, наявність механічної жовтяниці перед операцією та ін. [3,8,10,16,18].…”
Section: вступunclassified
See 2 more Smart Citations
“…Previous studies identified a multitude of risk factors involved in the occurence of postoperative pancreatic fistulas, factors such as: soft pancreas, small pancreatic duct, surgical technique, pancreato-digestive anastomosis, intraoperative blood loss, obesity, nutritional status, pathological type [10] [11].…”
mentioning
confidence: 99%